Stegomyia Indices and Risk of Dengue Transmission: A Lack of Correlation - Garjito, Triwibowo Ambar; Hidajat, Muhammad Choirul; Kinansi, Revi Rosavika; Setyaningsih, Riyani; Anggraeni, Yusnita Mirna; Mujiyanto,; Trapsilowati, Wiwik; Jastal,; Ristiyanto,; Satoto, Tri Baskoro Tunggul; Gavotte, Laurent; Manguin, Sylvie; et al. (Frontiers in Public Health, 2020)
Dengue is present in 128 countries worldwide and is still expanding. There is currently no treatment or universally approved vaccine available. Therefore, prevention and control of mosquito vectors remain the most efficient ways of managing the risk of dengue outbreaks. The Stegomyia indices have been developed as quantitative indicators of the risk of dengue outbreaks. However, conflictual data are circulating about their reliability. We report in this article the first extensive study on Stegomyia indices, covering 78 locations of differing environmental and socio-economic conditions, climate, and population density across Indonesia, from West Sumatra to Papua. A total of 65,876 mosquito larvae and pupae were collected for the study. A correlation was found between incidence and human population density. No correlation was found between the incidence of dengue and the Stegomyia indices.